Alteration of sperm protein profile induced by cigarette smoking. (10th June 2015) - Chen, Xiaohui; Xu, Wangjie; Miao, Maohua; Zhu, Zijue; Dai, Jingbo; Chen, Zhong; Fang, Peng; Wu, Junqing; Nie, Dongsheng; Wang, Lianyun; Wang, Zhaoxia; Qiao, Zhongdong; et al.
Abstract: Cigarette smoking is associated with lower semen quality, but how cigarette smoking changes the semen quality remains unclear. The aim of this study was to screen the differentially expressed proteins in the sperm of mice with daily exposure to cigarette smoke. The 2D gel electrophoresis (2DE) and mass spectrometry (MS) analyses results showed that the mouse sperm protein profile was altered by cigarette smoking. And 22 of the most abundant proteins that correspond to differentially expressed spots in 2DE gels of the sperm samples were identified. These proteins were classified into different groups based on their functions, such as energy metabolism, reproduction, and structural molecules. Furthermore, the 2DE and MS results of five proteins (Aldoa, ATP5a1, Gpx4, Cs, and Spatc1) were validated by western blot analysis and reverse transcriptase-polymerase chain reaction. Results showed that except Spatc1 the other four proteins showed statistically significant different protein levels between the smoking group and the control group ( P < 0.05). The expressions of three genes (Aldoa, Gpx4, and Spatc1) were significantly different ( P < 0.05) at transcription level between the smoking group and the control group. In addition, five proteins (Aldoa, ATP5a1, Spatc1, Cs, and Gpx4) in human sperm samples from 30 male smokers and 30 non-smokers were detected by western blot analysis. Two proteins (Aldoa and Cs) that are associated with energy production were found to be significantly altered, suggesting that these proteins may be potential diagnostic markers for evaluation of smoking risk in sperm. Further study of these proteins may provide insight into the pathogenic mechanisms underlying infertility in smoking persons.